Gyrodactylus ginestrae n. sp. (Monogenea: Gyrodactylidae), a parasite of the big-scale sand smelt, Atherina boyeri Risso, 1810 (Actinopterygii: Atherinidae) from the Black Sea - Kvach, Yuriy; Ondračková, Markéta; Seifertová, Mária; Hulak, Bohdan (Parasitology research, 2019)
We describe a new species, Gyrodactylus ginestrae n. sp., a parasite of the big-scale sand smelt (Atherina boyeri) from the Black Sea. This is the third monogenean species known from this fish host, found at 70% prevalence, but at relatively low abundance (1.9), on fish gills and fins. The new species is, both morphologically and genetically, most similar to G. salinae, which parasitizes the killifish Aphanius fasciatus (Cyprinodontidae) in the Mediterranean region. These species differ in the size of the haptoral hard parts and the number of small spines of the male copulatory organ. For molecular characterization, the internal transcribed spacer 1 (ITS1), 5.8S rRNA gene, and the internal transcribed spacer 2 (ITS2) were sequenced, completed by a fragment of the COII gene, thereby representing the first molecularly characterized gyrodactylid species from the Black Sea. Phylogenetic reconstruction based on the ITS1-5.8S-ITS2 sequence data indicated the position of G. ginestrae n. sp. in the marine "rugiensis" group of G. (Paranephrotus) and G. (Neonephrotus) subgenera which is part of the monophyletic "long ITS1" group. Taking into account the similarity of G. ginestrae n. sp. to several monogeneans from the Atlantic and Mediterranean regions, we suggest the Boreal-Atlantic origin of this species.
Keywords: Osmeriformes; Animals; Trematoda; ribozomální DNA; Gills; DNA, Ribosomal; Gulf of Odessa; druhová specificita; Black Sea; Species Specificity; žábry; DNA, Helminth; Gyrodactylidae; Phylogeny; DNA helmintů; ploutve zvířat; Animal Fins; Ponto-Caspian; zvířata; Brackish water; fylogeneze; Černé moře; Molecular study